2009
DOI: 10.1177/147323000903700622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of POSSUM in Predicting Post-Operative Morbidity in Patients Undergoing Pancreaticoduodenectomy

Abstract: The Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity (POSSUM) is a predictive scoring system for post-operative morbidity. The present study assessed the value of POSSUM in predicting post-operative morbidity following pancreaticoduodenectomy (PD). POSSUM scores were prospectively calculated for 265 consecutive cases of PD performed between 2005 and 2007. Expected morbidity was estimated based on POSSUM scores and was compared with observed morbidity. Patients were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In contrast, Deyle et al [15] reported that E-PASS was an ineffective predictor of complications following pancreatic resection. Similar contradictive results have been reported on the accuracy of POSSUM models in pancreatic resections [16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast, Deyle et al [15] reported that E-PASS was an ineffective predictor of complications following pancreatic resection. Similar contradictive results have been reported on the accuracy of POSSUM models in pancreatic resections [16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 71%
“…Zhang et al. analyzed 265 cases and revealed that POSSUM overestimated mortality rates especially in low‐risk groups. On the other hand, Pratt et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Postoperative mortality risk is typically <5% in high-volume institutions, [16][17][18][19][20][21][22][23][24] but morbidity remains high at 30-40%. [24][25][26][27][28][29][30][31][32][33] Relatively few studies have assessed the implementation of an ERAS programme following PD. 19,20,[34][35][36][37][38][39] Some studies have reported the feasibility and effect on reducing postoperative LoS and hospital costs.…”
Section: Introductionmentioning
confidence: 99%
“…An even larger study on 694 patients focusing on morbidity reported an AUC of 0.64 by POSSUM with significant overestimation of actual risk 14 , in line with the results of this study. In contrast, accurate prediction by POSSUM of morbidity following pancreatic resection has also been reported with an observed to expected morbidity ratio of 0.96 in 326 patients 15 and 0.91 in 265 patients 16 . An important feature of the POSSUM score is the incorporation of physiological, as well as operative, variables.…”
Section: Discussionmentioning
confidence: 99%